University education and its impact on human capital development in Nigeria - David, Idongesit; David, Eseohe Glory Okoedion; Okolie, Ugo Chucks (Studi sulla Formazione/Open Journal of Education, 2021)
Human capital has been recognized globally as one major factor that is responsible for the wealth of nations. Education in human capital theory plays an important role in promoting economic and social development; it is strong catalyst of equity and advancement. University education is thus meant to be development-oriented, whether in respect of the society or the individual and whether in physical or psychological dimensions. In Nigeria today, the high level of moral decadence among the students, injustice and unethical value system that pervade Nigerian universities’ system serve as indication deteriorating and degeneration of ethical values system that society desire for intense socio-economic development vis-à-vis peaceful co-existence in Nigeria. It is against this backdrop that this study investigates the impact of university education on human capital development in Nigeria. A descriptive method was adopted and data was collected via a survey of three hundred (300) respondents using non-probabilistic sampling techniques. Data collected were analyzed using correlation and linear regression analysis with the aid of Statistical Package for Social Science (SPSS) version 17. The results of the study showed that there is significant relationship between university education and human capital development. As predicted, the study also revealed that university education exerts a positive and statistically significant impact on human capital development in Nigeria. Requisite conclusion and recommendations were provided in the light of the theoretical and empirical findings.